Hyperthermic isolated limb perfusion as a treatment of advanced melanoma - Kopacz, Andrzej; Jastrzębski, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2001)
Increasing incidents of melanoma requires a new strategies of treatment in different stages of the disease. The isolated limb perfusion is one of them. This method is usually used for treatment of in-transit metastases. The perfusion is peformed under general anesthesia and is based on separation of limb circulation from systemic circulation. Caniulisation is peformed on the subclavian or axillar level in upper limb or on iliac, inguinal or popliteal level in lower limb. The dermal and subdermal venous vessels are pressed by Esmarch turniquets. The blood in extrasystemic circulation passes through oxygenator and heat exchanger. The circulation is forced by the peristaltic pump. The hyperthermia is one of the essential elements of the therapy in isolated limb perfusion. This element exerts on cytotoxic effects of cytotoxic drugs and produces an demage effects in melanoma cells. After reaching temperature of 42 o C, the cytostatic (melfalan usually) is administered into limb circulation. Tumor necrosis factor is more effective but its application is connected with several toxic effects. This paper discusses the technique of hyperthermic isolated regional limb perfusion, drugs used, therapeutic effects, side effects and diferent problems connected with this type of treatment.